KARAKTERISASI RESERVOIR PADA PENAMPANG TEGAK ANTAR SUMUR MENGGUNAKAN METODA SIMULASI ANNEALING DENGAN TAMBAHAN BATASAN DATA SEISMIK - Trikoranto, Herutama
One of the main problems in the description of reservoir properties is related to availability of sample data. Limitation in quantity as well as distribution of this data leads to unsatisfied realization of inter-well reservoir characterization. In the circumstances of this lacking of data, several number of geostatistics methods have been developed to estimate distribution of reservoir parameter in that unsampled location. Recent development in seismic data processing and analysis, that is seismic inversion, has been able to furnish a footstep to define such physical reservoir data in inter well vertical section. This inversion processing yields seismic impedance; an acoustic parameter that is a product of rock density and seismic wave velocity. A stochastic "cloud transform" method instead of deterministic ones will be applied to change this acoustic impedance to porosity. This work tries to integrate this stochastic procedure with Simulated Annealing Method (SAM) to optimize the result of porosity description in limestone reservoir. Spatial relationship between reservoir parameters will be formulated as semivariograms. Due to strong relationship between impedance and porosity, semivariogram in lateral direction will be derived from acoustic impedance data; whereas that in vertical direction will be defined from log data in reference wells It is not beyond our prediction that the realization of this research exhibits better result than that of previous work by Perez. Pearson coefficient calculated to quantify realization at a test-well gives the value of 0.61.